STUDENTS’ PERCEPTION TOWARDS THE USE OF SMARTPHONE IN LEARNING ACTIVITIES - Sumadi, Sumadi; Surlitasari Dewi, Desi (Foreign Language Instruction Probe, 2022)
The current study investigates students’ perception regarding the role of Smartphones in English language learning at MAN Buntet Pesantren. The researcher applied descriptive qualitative method for this research. The data gathered from interview, online questionnaires and document analysis. The result shows that mobile device that being used mostly is smartphone. In the classroom activities it being used to play music, translating, training speaking and listening, and browsing. Meanwhile, outside the classroom it is being used to conducting distance learning, for delivering materials, and collecting the assignment. The obstacles of implementing MALL are low connectivity, unsupported phone, high cost, risk of distraction, and risk of cheating. The last is students’ perception towards MALL was seen from the ease of use and usefulness of mobile device. In short, they seems to have good perception.